(untitled) (Revista Brasileira Multidisciplinar, 2026)
The aim of this study was to assess, after 1-year follow-up, the marginal bone alterations around dental implants placed by using the flapless guided surgery technique with and without immediate loading. For this, conventional loading was placed in 8 patients (G1), whereas immediate loading was placed in the other 8 patients (G2). Tomographic measurements of the buccal and palatal bone wall thickness and buccal, palatal, mesial, distal bone wall height were measured in the cone beam computed tomography after the surgery (T0) and 1 year after the prosthesis installation (T1). The results showed of the 16 patients treated, ten were female and six were men. There were statistically significant differences between T0 and T1 in both groups regarding buccal bone resorption (buccal-G1-P=0.0185;G2-P=0.0017), palatal bone resorption (palatal-G1-P=0.008) and loss of vertical bone height in the buccal (G1-P=0.0066;G2-P=0,0015), palatal (G1-P=0,0015;G2-P<0.001), mesial (G1-P=0.0029; G2-P=0.001), and distal (G1-P<0.002;G2-P<0.005) walls. Regarding the comparison between G1 and G2, there were no statistically significant differences for all parameters evaluated at time T0 and T1. This study indicates that the flapless guided surgery technique with or without immediate loading did not influence in the marginal bone loss around dental implants after 1-year follow-up.